1994
DOI: 10.1002/anie.199421841
|View full text |Cite
|
Sign up to set email alerts
|

Zaragozic Acid A/Squalestatin S1: Synthetic and Retrosynthetic Studies

Abstract: Step by step the first total synthesis was approached: of the zaragozic acids/ squalestatins showing potential therapeutic value for lowering the serum cholesterol concentration, zaragozic acid A/squalestatin SI (1), the most abundant member of a new class of naturally occurring products, has now been synthesized via the key intermediates 2 and 3. Initially the projected final sequence (2 → 1) was achieved, and the side chains attached to C1 and C6 were prepared through efficient asymmetric syntheses. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This new 4-step synthesis of alcohol 7 , in 22% overall yield and in 97% ee, has distinct advantages over previously reported asymmetric syntheses of this pheromone in terms of stereochemical purity, number of steps, and total yield . Furthermore, the chiral γ-methyl-α,β-enoate structural unit is present in many natural products, including steroids, macrolides, and squalestatins . The scalability of this short protocol was confirmed when 2.8 g of γ-methyl ester 3a was synthesized in 60% overall yield and 95% ee starting with commercial 3-phenylpropanal .…”
mentioning
confidence: 99%
“…This new 4-step synthesis of alcohol 7 , in 22% overall yield and in 97% ee, has distinct advantages over previously reported asymmetric syntheses of this pheromone in terms of stereochemical purity, number of steps, and total yield . Furthermore, the chiral γ-methyl-α,β-enoate structural unit is present in many natural products, including steroids, macrolides, and squalestatins . The scalability of this short protocol was confirmed when 2.8 g of γ-methyl ester 3a was synthesized in 60% overall yield and 95% ee starting with commercial 3-phenylpropanal .…”
mentioning
confidence: 99%
“…Compound 9 is the enantiomer of Nicolaousi ntermediate,w hich was initially synthesized in 12 steps with 81 % ee. [16] To further illustrate the usefulness of this methodology, we continued to explore its potential in the synthesis of gbutyrolactones (Scheme 3), which are important structural units of aw ide range of pharmacologically active molecules. [17] Ozonolysis of the desymmetrized product of 10 followed by hydroxy-directed Wittig reaction [18] afforded the unsaturated ester (4S,5S)-12 as asingle isomer with excellent d.r.…”
Section: Methodsmentioning
confidence: 99%
“…To introduce the (8R,9R)-diol functionality, lactone 41 was subjected to dihydroxylation conditions using ADmix-b, as established in the synthesis of fostriecin 1; however, these conditions turned out to be unsatisfactory in terms of reproducibility. After exploring various conditions, we eventually found that reaction of 41 with Super-AD-mix, 35 using the ligand for Sharpless asymmetric dihydroxylation [(DHQD) 2 PHAL] as a chiral ligand, resulted in highly diastereoselective dihydroxylation preferentially at the D 8 -double bond to give diol 42 together with its 6,7-dihydroxy isomer in a ratio of 87:13; however, very high regioselectivity was not observed in this case, unlike the dihydroxylation of 14 discussed above.…”
Section: Scheme 8 Preparation Of Aldehyde 33mentioning
confidence: 99%